Two Collaborative Projects for Coroplastic Research, V. The Work of the Academic Years 2018–2019 - Arthur Muller; Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
An international team of 7 researchers has been meeting biannually to collaborate on two projects that are envisaged as aids for coroplastic research. The first is provisionally titled The Handbook for Coroplastic Research, a tool designed for those new to the field of coroplastic studies. The second project has been nicknamed “Winter On-Line.” This concerns the creation of a searchable version of Franz Winter, Die Typen der figürlichen Terrakotten, (1903), in a wiki format